Treatment of Neurocysticercosis with Subarachnoid Cysts - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The medical treatment of 33 patients, 8 to 81 years (mean, 48y), with neurocysticercosis (NC) complicated by giant subarachnoid cysts (50mm or larger) and intracranial hypertension was evaluated at the Hospital de Especialidades, Mexico City.